Praktik Budidaya Padi Ladang Masyarakat Suku Tolaki di Desa Mata Wolasi Kecamatan Wolasi Kabupaten Konawe Selatan - Iriyanto, Eri; Widayati, Weka; Taridala, Sitti Aida Adha (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
This research was motivated by the problem of low productivity of paddy fields cultivated by Tolaki in the village of Mata Wolasi. The purpose of this study was to determine the activities undertaken during the production process carried out. Research carried out in July 2017. Types of data used were primary data and secondary data. Data analysis was used by descriptive qualitative. The results showed that the practice of dryland paddy cultivation Tolaki community in District Wolasi done with traditional tools and tools ranging from land processing to harvest. Processing of land, planting, and harvesting was done in mutual assistance, while weed cleaning and plant pest control were done by farmer and farmer's wife. The cultivation time was done for one to four months, planting done one day, weed cleaning is done for one month and harvest is done for two to three days. The practice of paddy field cultivation by Tolaki community doesn’t use fertilizer and not in accordance with a recommended suggestion.